Desain dan Implementasi Situs Web Sederhana Menggunakan HTML dan CSS - Muh. Arfah Wahlil Pratama; Wahda Mutmainnah; Khusnul Khatimah; Yudhika Setiawan; Aril Adila Yusuf; Muh Afriansyah; Andi Nurfadillah (Jurnal Teknologi dan Bisnis Cerdas, 2026)
This study aims to demonstrate the design and implementation of a simple static website using HTML (HyperText Markup Language) and CSS (Cascading Style Sheets) without additional frameworks. In the digital era, the ability to create basic websites has become essential, especially for beginners in web development. This study addresses this need by focusing on content structure using HTML and visual presentation using CSS. The development method employed is the waterfall model, which systematically includes the stages of requirements analysis, design, implementation, and testing. The tools used include Visual Studio Code as the text editor and Google Chrome as the web browser for testing. The results demonstrate the successful development of a simple profile website consisting of a navigation header, main content section, and footer, utilizing HTML5 semantic elements and CSS styling to achieve a responsive and visually appealing layout. The practical implementation emphasizes simplicity and maintainability, with HTML code handling the structural foundation and CSS managing visual presentation, resulting in a functional and easily maintainable website. The study confirms that pure HTML and CSS are sufficient for developing static website projects, providing a solid foundation for beginners. Recommendations for future development include incorporating JavaScript for enhanced interactivity and dynamic functionality. This study provides a practical guide for students and novice developers in understanding fundamental web development concepts.